The effect of preferred music on physiological parameters of pain in - Zolfaghari, mitra; Ajri Khameslou, mehdi; Zaherimogadam, masoumeh; Ajri Khameslou, elham; farokhnezhad, pouya (Advances in Nursing & Midwifery, 2015)
Background & Aim: Pain is a major unpleasant experience for patients in Intensive care unit. The aim of this study was to investigate the effect of listening to preferred music on physiological parameters of unconscious patients as assessment indicator of pain. Methods & Materials: In this clinical trial study, 72 unconscious patients were selected form intensive care units of Sina and Imam Khomeini hospitals in Tehran by convenience sampling method. Patients were randomly allocated into two groups (intervention and control groups). In intervention group, patients listened to music selected by their family members for 30 minutes a day for three consecutive days. intervention (music) patients for 30 minutes without any intervention and rest in the bed. Patients in control group did not listen to music. Physiological parameters including systolic blood pressure, diastolic blood pressure, mean arterial pressure, heart rate and peripheral capillary oxygen saturation (spo2) were obtained 10 minutes before and 30 minutes after intervention. Data were analyzed using SPSS V.18 software. Results: There was no significant difference between two groups in terms of physiological parameters before intervention. There was a statistically significant decrease in systolic blood pressure (P=0.006) and mean blood pressure (P= 0.038) of patients in intervention group. There was a significant increase of heart rate among patients in intervention group . There was no difference between the two groups in terms of diastolic blood pressure. Conclusion: Results of this research provide evidence to serviceable the use of music in this patient Keywords: Pain, Music, vital signs, physiological parameters, unconscious